Development of an alternative synthesis of 2-acetamido-2-deoxy-L-altruronic acid: an unusual sugar found in the O-specific polysaccharide of Shigella sonnei - Anderson, Kirstin P C (Department of Chemistry, 2017)
A new synthetic route has been explored for the preparation of derivatives of 2-acetamido-2-deoxy-L-altruronic acid (L-AltNAcA). This is a rare sugar found together with 2-acetamido-4-amino-2,4-dideoxy-D-fucose(D-FucNAc4N) in the repeating unit of Shigella sonnei. Derivatives are needed inter alia for chemical and spectroscopic calibration standards, and as building blocks for preparing oligomeric subunits of the O-polysaccharide antigen for possible incorporation into a synthetic glycoconjugate vaccine. Two synthetic routes were investigated. The first route successfully repeated a published four step sequence converting diacetone-D-glucose to 1,6-anhydro--L-idopyranose in a 38% yield overall, and a further selective benzylation at O-3. Attempts to discriminate between O-2, O-3 and O-4 using low temperature acylation or alkylation conditions were unsuccessful, but modest selectivity for the 4-benzoate was observed in a Bu₂SnO-mediated benzoylation, although this product could not be easily separated from other mono-benzoates. The second route started from N-acetyl-D-glucosamine which was successfully converted in the first step to 2-methyl-(1,2-dideoxyl-5,6-O-isopropylidene-α-D-glucofurano)-[2,1-d]-2-oxazoline. The oxazoline and dioxolane units could be selectively manipulated in a series of steps to afford 2-acetamido-2-deoxy-3-O-benzyl-6-O-t-butyldimethylsilyl-α-D-glucofuranosyl acetate in a 41% yield over four steps. This is a key synthetic intermediate in which the 5-OH is available for the required inversion step. During this study, an unusual minor side-product, 1,6-anhydro-2-acetamido-O-acetyl-2-deoxy-3-O-benzyl-α-D-glucofuranose, was isolated. While this was also a potentially useful intermediate, having only the 5-OH unprotected, it proved not possible to find conditions for optimizing this product. Inversion of configuration at C-5 in the 6-O-silylated glucofuranose was attempted via the 5-O-triflate and 5-O-mesylate: the triflate formed but was displaced in situ by the solvent pyridine to give an unusual 5-pyridinium derivative, while the mesylate was stable but unreactive towards subsequent SN2 inversion. These outcomes were attributed to the steric congestion imposed by the combination of the 3,4-cis-disubstitution of the furanose ring and the very bulky silyl substituent at O-6. While the goal of preparing L-AltNAcA was not achieved via these approaches, useful insights have been contributed towards the ongoing study.